2003
DOI: 10.1002/bjs.4014
|View full text |Cite
|
Sign up to set email alerts
|

Combined evaluation of mucin antigen and E-cadherin expression may help select patients with gastric cancer suitable for minimally invasive therapy

Abstract: Background: MUC1 mucin is known to be highly expressed in carcinomas that show invasive growth and poor prognosis. Impairment of adhesion molecule E-cadherin expression has been widely accepted as a critical event for cancer invasion and metastasis. The present study evaluated the combination of mucin and E-cadherin status as a possible predictor of patients suitable for minimally invasive therapy for gastric cancer.Methods: Two hundred and nine paraffin-embedded specimens of gastric carcinoma (141 early, 68 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…There are no significant differences between two groups (P =0.95) appear to have a favorable outcome. We here showed expression of MUC5AC and MUC2 demonstrated in 60 (33.9%) and 60 (33.9%) of the 177 gastric cancers, which is compatible with previous studies (Lee et al 2001;Lee et al 2003;Tanaka et al 2003;Pinto-de-Sousa et al 2002). Villin is a useful intestinal phenotypic marker detected in the brush border on luminal surfaces and is associated with Cdx2 expression (Tatematsu et al 2003;Werling et al 2003).…”
Section: Discussionsupporting
confidence: 77%
“…There are no significant differences between two groups (P =0.95) appear to have a favorable outcome. We here showed expression of MUC5AC and MUC2 demonstrated in 60 (33.9%) and 60 (33.9%) of the 177 gastric cancers, which is compatible with previous studies (Lee et al 2001;Lee et al 2003;Tanaka et al 2003;Pinto-de-Sousa et al 2002). Villin is a useful intestinal phenotypic marker detected in the brush border on luminal surfaces and is associated with Cdx2 expression (Tatematsu et al 2003;Werling et al 2003).…”
Section: Discussionsupporting
confidence: 77%
“…While we noted its highest expression in the well and moderately differentiated tubular carcinoma which supported the view on its contribution to tubular structure formation [19] . Although some studies showed that MUC1 expression in gastric cancers was negatively correlated with the expression of E-cadherin [20] , we found the positive relationships between them, what's more, the correlation of MUC1, MUC2 and Ecadherin were first studied by us. Both MUC1 and MUC2 might contribute to the progress of gastric cancer, and they might restrain the role of E-cadherin.…”
Section: Discussionmentioning
confidence: 56%
“…This impaired adhesion status is clearly correlated with a haematogenous spread of the primary tumor cells, is an independent predictive marker for lymph node or distant metastasis, and for disease recurrence of many kinds of cancers including breast, colorectal, gastric, colorectal, esophageal, prostate, etc. (Aoki et al 2003;Asgeirsson et al 2000;Bankfalvi et al 2002;Chow et al 2001;Ikeguchi et al 2000;Loric et al 2001;Rhodes et al 2003;Tanaka et al 2003). It is also a significantly poor prognostic factor for survival (Shnayder et al 2001;Sugio et al 2002).…”
Section: E-cadherin and Beta-cateninsmentioning
confidence: 91%